General Pharmacological Profile of the Novel Muscarinic Receptor Agonist SNI-2011, a Drug for Xerostomia in Sjögren’s Syndrome - Arisawa, Hirohiko; Imai, Eiichi; Fujise, Nobuaki; Fukui, Kenji; Masunaga, Hiroaki (Arzneimittelforschung, 2002)
A novel muscarinic receptor agonist, SNI-2011 ((±)-cis-2-methylspiro[1,3-oxa-thiolane-5,3’-quinuclidine] monohydrochloride hemihydrate, cevimeline, CAS 153504-70-2), is a candidate therapeutic drug for xerostomia in Sjögren’s syndrome. The general pharmacological properties of this drug on general behavior and the central nervous system were investigated in mice, rats and cats.General behavior: When SNI-2011 was administered orally to mice at 100 mg/kg, mydriasis, a decrease of spontaneous motor activity, tremor, convulsions, salivation, abnormal posture, abnormal gait, reduced grip strength and reduced response against external stimulating were observed, and 2 out of 6 animals died. At 10 mg/kg or lower, no particular sign was observed except mydriasis, which appeared to be caused via the peripheral muscarinic acetylcholine receptors.Central nervous system: SNI-2011 had no effect on the motor coordination in mice. Hypothermia was observed in rats and reduced spontaneous motor activity, analgesia and enhanced maximum electroshock-induced convulsions were observed in mice after oral administration of 30 mg/kg SNI-2011. Slight increase in the rate of v-wave band in the hippocampal EEG of rats and spinal multisynaptic reflexes in cats were observed after intravenous injection of 10 mg/kg SNI-2011. At an oral dose of 10 mg/kg, prolongation of thiopental-induced sleeping time in mice was observed. The prolongation of sleeping time was inhibited by a peripheral muscarinic antagonist. These results suggest that SNI-2011 has muscarinic effects on general behavior and the central nervous system at the doses approximately 10-fold higher than the effective doses needed for saliva secretion.
Keywords: CAS 153504-70-2; Cevimeline; Muscarinic agonist; Sjögren’s syndrome; SNI-2011, general pharmacology